CSR education in economia Aziendale Curricula: an overview - Andrea Venturelli; Roberta Fasiello; Simone Pizzi (Administrative Sciences, 2021)
In the last few years, policymakers have underlined the need for new soft and hard skills about corporate social responsibility (CSR). The main debate about CSR education has been driven by the 2030 Agenda, which explicitly recognized Higher Education Institutions (HEIs) as having a pivotal role. In particular, many academics started to develop qualitative and quantitative studies to evaluate the integration of CSR contents in business schools' curricula. The paper aims to contribute to the existing debate through the analysis of the contribution provided by Italian HEIs to CSR Education. In particular, we adopted qualitative methods to evaluate the specific contribution provided by Economia Aziendale scholars.
Keywords: 350; education; Economia Aziendale; business ethics; CSR3; SDGs